Improving the thermal stability and luminescent efficiency of (Ba,Sr)3SiO5:Eu2+ phosphors by structure, bandgap engineering and soft chemistry synthesis method - Liu, Hongmin; Liang, Hongwei; Zhang, Wenye; Zeng, Qingguang; Wen, Dawei (Chemical Engineering Journal, 2021)
[Display omitted] •Comprehensively analyzing the thermal quenching properties of (Ba,Sr)3SiO5:Eu2+.•The emission intensity and thermal stability of (Ba,Sr)3SiO5:Eu2+ were improved by structure and bandgap engineering.•The sol-gel synthesized BaSr2SiO5:Eu2+ showed excellent thermal performance, only 5% loss of intensity at 150 °C.•The as-synthesized phosphor was proved to improve the correlated color index and color rendering index. The quantum yield and thermal stability are significant properties for phosphors, determining the luminescence efficiency of the devices for indoor lighting, displays backlight and near-infrared (IR) sensor applications. It is well known that the large bandgap and Debye temperature (Structure rigidity) values are beneficial to high thermal resistance. Here, the crystal structure, luminescence, thermal quenching property, bandgap and structural rigidity of (Ba,Sr)3SiO5:Eu2+ were studied via Rietveld refinement, temperature-dependent photoluminescence spectra and first-principle calculations. The quantum yield and thermal stability of (Ba,Sr)3SiO5:Eu2+ were increased by ~17% and 14%, respectively, via the combination of structure and bandgap engineering. These properties were further optimized by sol-gel synthesis process, achieving 28% increase of emission intensity compared to the same composition synthesized by a solid-state method and only 5% loss of luminescence intensity at 150 °C. By adding the as-synthesized phosphors, the correlated color temperature and color rendering index of the LED device were lower and higher, respectively, indicating the potential value in practice.